1980
DOI: 10.1055/s-0038-1650055
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Dipyridamole Prophylaxis of Sickle Cell Disease Pain Crises

Abstract: We have previously reported that long term daily administration of aspirin-dipyridamole significantly improved laboratory findings indicative of disease activity in patients with sickle-cell disease. The laboratory index most influenced by platelet inhibitory drug therapy was the plasma concentration of high molecular weight fibrin(ogen) complexes (HMWFC), a moiety which reflects the rate of fibrin formation in vivo. Although improvement of laboratory findings with therapy was accompanied by apparent clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
4

Year Published

1984
1984
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 1 publication
(1 reference statement)
0
36
0
4
Order By: Relevance
“…While a single study found thrombocytosis to be associated with impaired cognitive dysfunction in children with SCD (74), epidemiological studies have not reported thrombocytosis to be associated with increased overall severity of SCD, (75)(76)(77)(78)(79)(80), although such studies did not consider platelet size or mass. Despite the evidence for increased platelet consumption during painful crises (9), there are few data to support a role for platelets in microvascular obstruction, and small studies of aspirin, aspirin with dipyridamole, and ticlopidine failed to show a definitive benefit in reducing the frequency of pain crises (20)(21)(22)(23)(24). One potential link is through platelet surface expression of P-selectin and the recruitment of leukocytes since the latter have been implicated in contributing to vasoocclusion (81;82).…”
Section: Discussionmentioning
confidence: 99%
“…While a single study found thrombocytosis to be associated with impaired cognitive dysfunction in children with SCD (74), epidemiological studies have not reported thrombocytosis to be associated with increased overall severity of SCD, (75)(76)(77)(78)(79)(80), although such studies did not consider platelet size or mass. Despite the evidence for increased platelet consumption during painful crises (9), there are few data to support a role for platelets in microvascular obstruction, and small studies of aspirin, aspirin with dipyridamole, and ticlopidine failed to show a definitive benefit in reducing the frequency of pain crises (20)(21)(22)(23)(24). One potential link is through platelet surface expression of P-selectin and the recruitment of leukocytes since the latter have been implicated in contributing to vasoocclusion (81;82).…”
Section: Discussionmentioning
confidence: 99%
“…Chaplin et al 33 conducted a clinical study to determine if dipyridamole combined with aspirin would reduce the frequency and severity of vaso-occlusive episodes and mitigate the associated coagulation abnormalities. They treated 3 patients for several years in a nonblinded, longitudinal crossover study, accruing a total of 340 patient weeks on medication and 315 weeks off drug.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study of low-dose acenocoumarol in 22 patients with SCD demonstrated significant decreases in prothrombin fragment 1.2 levels, thrombin-antithrombin complexes and D-dimer fragments, but displayed no impact on the occurrence of vasoocclusive crises (167). Finally, no clear clinical benefit was observed in small, nonrandomized clinical studies of low dose aspirin (168) and aspirin plus dipyrimadole (169).…”
Section: Anticoagulant Therapymentioning
confidence: 99%